Evaluación del control interno del Departamento Financiero del Gobierno Autónomo Descentralizado Parroquial La Unión, cantón Babahoyo - Velásquez Garaicoa, Nadia Madeline (2020)
The internal control system is a tool that every institution must use, since it allows for proper monitoring of the way in which the processes carried out in the different departments that make up the institution are carried out. This case study focuses on the evaluation of the internal control of the financial department of the La Unión Parish Decentralized Autonomous Government, Babahoyo Canton; The parish GAD, being a public institution, needs to have a correct control system; Since this will allow the detection of deficiencies and the possibility of applying the necessary corrections, and in this way fulfill the institutional objectives set. Within the control system is financial control; which is an entity of vital importance within the organization and management of entities, since this control tool allows to be able to bring an order in the management of the financial part of the institution, that is to say that the internal financial control will allow to see if economic resources are adequately managed. The internal control of the financial department of the La Unión Parish Decentralized Autonomous Government, Cantón Babahoyo, is linked to the strategic planning of the organization, this allows to determine if the institutional goals and objectives are laudable and if the investment of the financial resources of the institution is guaranteed and they do not run the risk of getting lost, putting them in an unfavorable situation for the organization.